Pengaruh Motivasi, Tingkat Pendidikan, Budaya Organisasi, Lingkungan Kerja dan Insentif terhadap Kinerja Guru dan Karyawan SMK Yayasan Pendidikan Colomadu Kabupaten Karanganyar - Widiasmara, Anny (Widya Warta, 2014)
This research aims to seek the influences of motivation, education level, organizational culture, work environment, and incentive toward the performance of teachers and noneducational staffs at Senior Vocational School (SMK) of Colomadu Education Foundation in Karanganyar. So far, the fact shows that the performance of teachers and non- educational staffs at Senior Vocational School (SMK) of Colomadu Education Foundation in Karanganyar decreases significantly. The data of the study are the primary ones taken with the use of questionnaires. The questionnaires contain a list of questions which should be answered by 67 teachers and non- educational staffs of Senior Vocational School (SMK) of Colomadu Education Foundation in Karanganyar. The data were analyzed applying instrument test, classical assumption test, hypothesis test with double linier regression, t – test, F – test and R2 – test. The analysis on the data showed that (1) the result of instrument test was valid and reliable; (2) the result of classical assumption test indicated normal distribution of the data and neither multicolinierity, heterekedostisity, nor autocorrelation happened; (3) the result of hypothesis test with double linier regression revealed Y = 12,366 + 0,450 X1 + 0,135 X2 + 0,315 X3 – 0,149 X4 + 0,169 X5 + e. The equation above proved that motivation, education level, organizational culture, and incentive had positive effect toward the performance of teachers and non- educational staffs at Senior Vocational School (SMK) of Colomadu Education Foundation in Karanganyar. Whereas, work environment had negative effect toward the performance of teachers and non- educational staffs at Senior Vocational School (SMK) of Colomadu Education Foundation in Karanganyar. The t – test result of each variable had partial effecf; while, the F – test result showed simultaneous effect with the F result = 79,642 > F table 2,509. The R2 – test result was 0,856 or 85,6%, which means that dependent variable varieties of the performance of the teachers and non- educational staffs can be clarified by dependent variable varieties of motivation, education level, organizational culture, work environment, and incentive toward the performance of teachers and noneducational staffs = 85,6%. The rest can be explained by the other variables which are not included within the regression model, such as leadership and work experience.